A pre-lithiation silicon-carbon composite material and preparation method thereof
By passivating and carbon coating the core surface interface of pre-lithiated silicon-carbon composite materials, the problems of low first efficiency, fast capacity fading, and poor cycle stability of silicon-carbon composite materials in lithium-ion batteries are solved, achieving high efficiency, Stable electrochemical performance.
Patent Information
- Application Number
- CN202411471642.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing silicon-carbon composite materials have problems such as low first-term efficiency, fast capacity attenuation and poor cycle stability in lithium-ion batteries, which are mainly due to the material structure failure caused by poor conductivity of silicon element and volume changes.
By passivating the surface interface of the pre-lithiated silicon carbon core, a layer of artificial SEI film is formed to enhance the ion conductivity and mechanical strength, and the uniformity and integrity of the material are improved through carbon coating.
The Coulombic efficiency exceeded 100% for the first time, which improved the cycle performance and rate stability of lithium-ion batteries and extended the service life of the battery.
Smart Images

Figure CN118983426B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a pre-lithiation silicon-carbon composite material and a preparation method thereof. Background Art
[0002] Silicon has a high theoretical specific capacity (4200mAh / g) and a low lithium insertion potential. It is one of the most promising materials for the negative electrode of lithium-ion batteries. It is also abundant in the earth and has a low cost. However, the silicon material is accompanied by a serious volume change (~300%) during the lithium insertion and extraction process, which leads to the destruction and pulverization of the material structure, and then causes the electrode to crack and the active material to fall off the current collector. After multiple cycles, the capacity decays rapidly, which limits the application of silicon materials in the field of lithium-ion batteries.
[0003] In the prior art, silane gas is thermally decomposed at high temperature to form silicon and then filled into a carbon carrier with a porous structure to form a silicon-carbon composite material filled with nano-silicon, which has a high first coulombic efficiency and improved electrochemical performance. However, there is a large amount of nanostructured silicon in the silicon-carbon composite material prepared by the above method, and the silicon itself has extremely poor conductivity, and still undergoes a large volume change during the lithium insertion and delithiation process, resulting in limited improvement in the electrochemical performance of the material, such as cycle stability and rate. Therefore, it is urgent to explore new strategies to solve the problems of low first efficiency, fast capacity decay, and poor cycle stability of silicon-based materials.
[0004] CN117996050A discloses a lithium silicon carbon composite negative electrode material and a preparation method thereof, the preparation method comprising the following steps: step 1, under an inert atmosphere, placing porous hard carbon powder into a deposition furnace, heating to 400-600°C, charging lithium source and silicon source into the furnace, and depositing pore-filling material in the pores of the porous hard carbon particles to obtain a core material; step 2, adjusting the furnace temperature to 400-650°C, charging a carbon source, coating amorphous carbon on the surface of the core material, and obtaining a lithium silicon carbon composite negative electrode material through screening and demagnetization.
[0005] CN118213518A discloses a method for preparing a lithium-doped silicon-carbon composite material, comprising the following steps: Step S1: adding biphenyl to a tetrahydrofuran mixed organic solvent with a volume ratio of tetrahydrofuran: methoxy-nonafluorobutane = 1:10 to prepare an organic solvent of 0.5-5wt% in an inert atmosphere according to a mass ratio of porous carbon: metallic lithium: organic solvent = 100: 5-15: 500-1500, adding metallic lithium, dissolving it at a temperature of 25-60°C for 12-72h, then adding porous carbon, dispersing it evenly, performing a pre-lithiation reaction at a temperature of 25-60°C for 12-72h, filtering, and vacuum drying the obtained filter residue at 80°C for 24h, and obtaining the obtained material. Transfer to a tube furnace, introduce argon to exhaust the air in the tube, heat to 500-800°C, introduce carbon dioxide gas at a flow rate of 100-500ml / min for 60-600min to obtain lithium-doped porous carbon; Step S2: Transfer the lithium-doped porous carbon to a fluidized bed, heat to 400-600°C, introduce a silane gas mixture with a volume ratio of silane gas to argon gas = 1:9, introduce it at a flow rate of 100-500ml / min for 60-600min to obtain an intermediate, cool the intermediate to 200-300°C, introduce an unsaturated hydrocarbon gas mixture with a volume ratio of unsaturated hydrocarbon to oxygen = 10:1-3, and obtain a silicon-carbon precursor material;
[0006] Step S3: Mix the silicon-carbon precursor material and asphalt evenly according to the mass ratio of silicon-carbon precursor material: asphalt = 100: 5-10, heat to 250-350°C and keep warm for 1-3h, heat to 800-1100°C and keep warm for 1-3h, cool to room temperature, and crush to 3-7µm to obtain a lithium-doped silicon-carbon composite material.
[0007] The SEI formed by the above-mentioned traditional pre-lithiation process is a metastable organic compound and cannot maintain cycle stability by increasing the mechanical integrity of the coated carbon layer. Summary of the invention
[0008] In order to solve the above defects of silicon-carbon composite negative electrode materials in the prior art, the present invention performs corresponding passivation treatment on the surface interface of the pre-lithiated silicon-carbon core, and forms an artificial SEI film by in-situ polymerization on the surface of the silicon-carbon core, which has excellent ion conductivity and mechanical strength, further reduces expansion and lithium loss, and also provides a more complete interface platform for subsequent carbon coating, thereby improving the uniformity and integrity of the coating. In view of this, the present invention is specially proposed.
[0009] The purpose of the present invention is to provide a pre-lithiation silicon-carbon composite material, which pre-supplements lithium on the carbon skeleton to form a "lithium reservoir" through pre-lithiation technology. Since no residual alkali is produced, the first coulomb efficiency is increased to more than 100% without affecting the material processing performance, and the pre-lithiation silicon-carbon core is subjected to liquid phase passivation treatment to further improve the cycle performance of lithium-ion batteries. The present invention achieves the above purpose through the following technical solutions:
[0010] A pre-lithiation silicon-carbon composite material is a three-layer composite structure, which comprises, from the inside to the outside, a pre-lithiation silicon-carbon core, an intermediate passivation layer, and a carbon coating layer; the pre-lithiation silicon-carbon core is obtained by compounding a pre-lithiation agent and porous carbon and then undergoing silicon deposition; the silicon-carbon core contains 40-70wt% of nano silicon particles; the intermediate passivation layer is obtained by first subjecting the silicon-carbon core material to oxygen-containing gas calcination treatment and then to silane coupling agent surface modification treatment, wherein the silane coupling agent contains C6-C16 straight chain, branched chain, or cycloalkane.
[0011] The present invention also provides a method for preparing the pre-lithiation silicon-carbon composite material, comprising the following steps:
[0012] (S1) uniformly mixing a pre-lithiation reagent solution and porous carbon, and after sufficient pre-lithiation, performing solid-liquid separation and solid-phase calcination to obtain a pre-lithiation carbon substrate; placing the pre-lithiation carbon substrate in a reaction furnace, introducing a mixed gas I of silane gas and an inert gas under an inert atmosphere, and performing silicon deposition under heating conditions to obtain a silicon-carbon core material;
[0013] (S2) introducing a mixed gas II of oxygen-containing gas and inert gas into the reaction furnace, heating to 500-800° C. to heat-treat the silicon-carbon core material obtained in step (S1), pulverizing the material after cooling, dispersing the pulverized particles in an alcohol aqueous solution, adding an alcohol aqueous solution containing a silane coupling agent, and reacting to obtain a passivated silicon-carbon material; the long carbon chain silane coupling agent contains a C6-C16 straight chain, branched chain, or cycloalkane;
[0014] (S3) The passivated silicon-carbon material is carbon-coated to obtain a pre-lithiation silicon-carbon composite material.
[0015] Furthermore, in step (S1), the pre-lithiation reagent is a complex of lithium and an aromatic compound, and the aromatic compound is selected from at least one of biphenyl, dimethylbiphenyl, naphthalene, anthracene, and phenanthrene; the pre-lithiation is to immerse the porous carbon in a solution containing the pre-lithiation reagent, react at 40-50°C for 10-20h, and sinter the obtained slurry.
[0016] Furthermore, the solution containing the pre-lithiation reagent is obtained by reacting a lithium source and an aromatic compound in an organic solvent, the lithium source is selected from at least one of lithium element, lithium carbonate, and lithium hydroxide, the aromatic compound is selected from at least one of biphenyl, dimethyl biphenyl, 4,4'-di-tert-butyl biphenyl, naphthalene, anthracene, and phenanthrene, and the organic solvent is selected from at least one of tetrahydrofuran, 2-methyltetrahydrofuran, diethylene glycol dimethyl ether, and methyl tert-butyl ether; the sintering temperature is 500-700°C, and the sintering time is 5-10h.
[0017] Furthermore, in step (S1), the specific surface area of the porous carbon is 1500-2500 m 2 / g.
[0018] Furthermore, in step (S1), the amount of the pre-lithiation agent is 5-10 wt % of the mass of the porous carbon.
[0019] Further, in step (S1), silane is selected from at least one of monosilane, disilane, trichlorosilane and dichlorosilane, and the amount of silane gas introduced satisfies that the mass of silicon in the obtained silicon-carbon core accounts for 40-70wt%. The inert atmosphere is at least one of nitrogen, argon and helium. In the mixed gas I, the volume ratio of silane gas to inert gas is 1:1-4.
[0020] Furthermore, in step (S1), the heating condition during silicon deposition is 500-900°C.
[0021] Further, in step (S2), the oxygen-containing gas is selected from at least one of air, oxygen, carbon dioxide, carbon monoxide, sulfur dioxide, water vapor, methanol vapor and ethanol vapor; in mixed gas II, the oxygen-containing gas accounts for 1-5% of the volume of mixed gas II; the oxygen-containing gas can also be air, if it is air, then oxygen accounts for 1-5% of the volume of mixed gas II; the heat treatment time is 10-30min. When passivation is performed, the proportion of oxygen-containing gas in mixed gas II is not easy to be too high, and the heat treatment time is not easy to be too long, otherwise it is easy to cause excessive consumption of silicon-carbon core nano-silicon and lead to a decrease in capacity. The purpose of introducing oxygen-containing gas under heating conditions is to oxidize the surface silicon of the silicon-carbon core so as to provide corresponding bonding sites for subsequent silane coupling agent reactions.
[0022] Furthermore, in step (S2), the crushing method includes but is not limited to ball milling, high-speed crushing, air flow crushing, etc. The particle size of the crushed particles is 1-30 μm, preferably 5-20 μm.
[0023] Furthermore, in step (S2), the alcohol aqueous solution is a mixture of at least one of methanol, ethanol, propanol and water, wherein the alcohol accounts for 50-70wt%; the ratio of the alcohol aqueous solution to the crushed particles is 5-8mL:1g.
[0024] Furthermore, in step (S2), the alkane coupling agent is selected from at least one of cyclohexylmethyldimethoxysilane, dodecylmethyldimethoxysilane, and hexadecylmethyldimethoxysilane; the concentration of the alcohol aqueous solution of the silane coupling agent is 5-10wt%, and the amount of the alcohol aqueous solution of the silane coupling agent satisfies the mass ratio of the silane coupling agent to the crushed particles of 0.2-0.3:1. The alkane coupling agent has cycloalkanes above C6 or chain alkanes above C12, so that a uniform passivation layer can be formed on the surface to improve the cyclic stability of the material.
[0025] The bonding mechanism of silane coupling agent and silicon-based core material is Si-OH shrinkage bonding, so the silicon material must first be oxidized to form Si-OH functional groups, and then the Si-OH on the silane coupling agent can react with it to form a relatively uniform organic passivation layer on the surface. The oxidation process of the silicon material is actually creating suitable functional group binding sites for the subsequent coupling agent to bind, so that the passivation layer and the core silicon material have a corresponding bonding relationship rather than a physical bonding effect, and its bonding strength is higher and the film layer is more uniform.
[0026] Further, in step (S3), the carbon coating is conducted by introducing a carbon-containing process gas and heating at 500-800°C, wherein the carbon-containing process gas is selected from at least one of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, acetylene, propyne, and butyne. The amount of carbon-containing process gas introduced is such that the thickness of the carbon coating layer is 1-10 nm.
[0027] The present invention also provides a lithium-ion battery, wherein the negative electrode comprises the pre-lithiation silicon-carbon composite material.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] The pre-lithiation silicon-carbon composite material provided by the present invention has a core-shell structure, including a pre-lithiation silicon-carbon core, a passivation layer and a coating layer. The pre-lithiation silicon-carbon core forms a "lithium reservoir" by reacting a lithium-containing reagent with a strong reducing ability with a carbon substrate, thereby storing lithium so that it can continuously replenish lithium loss, and play the role of a lithium supplement to compensate for the first coulomb efficiency reduction caused by the formation of positive and negative electrode CEI, SEI and irreversible "lithium capture" in the first cycle, and even achieve a silicon-carbon negative electrode material with a first efficiency exceeding 100%. And the carbon substrate is used as a buffer medium to adjust the volume change of silicon in lithium insertion / delithiation, release the mechanical stress of silicon, and improve the cycle performance of the silicon-carbon composite material; the passivation layer passivates the silicon in contact with the electrolyte, so that it is first partially oxidized and then bonded with a silane coupling agent to form a uniform and dense organic passivation layer to stabilize the reversible performance of the battery; the carbonization layer improves the conductivity of the silicon-carbon composite material and improves the first coulomb efficiency. The above-mentioned pre-lithiation silicon-carbon core, passivation layer and coating layer generally improve the performance of the silicon-carbon negative electrode material.
[0030] The pre-lithiation silicon-carbon composite material provided by the present invention provides a negative electrode material with better performance for the battery, expands the use places and conditions of the battery, and promotes the development of downstream industries.
[0031] The battery provided by the present invention has a first-cycle charging capacity of >1800 mAh / g, a first-cycle coulombic efficiency of >100%, and excellent cycle stability at a 1C rate, which can effectively improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention;
[0033] Figure 2 This is an element distribution diagram of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention;
[0034] Figure 3 This is a first cycle charge and discharge voltage curve of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention;
[0035] Figure 4 This is the XRD diagram of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. The embodiments are only used to illustrate the present invention by way of example, and the present invention is not limited to the following embodiments.
[0037] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0038] Example 1
[0039] (S1) The porous carbon (BET = 1800m 2 / g) is added to an aryl lithium reagent solution, wherein the lithium source of the aryl lithium is lithium, the aryl compound is biphenyl, the solvent is tetrahydrofuran, the aryl lithium reagent is 10wt% of the mass of the porous carbon, and the reaction is stirred at a temperature of 50°C for 15h to obtain a slurry with a solid content of 30%, and the slurry is sintered at a temperature of 600°C for 8h to achieve pre-lithiation of the porous carbon; the pre-lithiated porous carbon is put into a reactor, and under a nitrogen atmosphere, the temperature is raised to 600°C at a heating rate of 10°C / min, and then a mixed gas I of monosilane gas and nitrogen gas in a volume ratio of 1:4 is introduced to perform silicon deposition to obtain a silicon-carbon core material, and the mixed gas flow rate and deposition time are controlled to make the silicon content of the silicon-carbon core material 51.2wt%, and the gas is cooled and stopped from being introduced into the mixer and switched to nitrogen;
[0040] (S2) introducing a mixed gas II of nitrogen and oxygen in a volume ratio of 99:1 to heat treat the silicon-carbon core material, the heat treatment temperature is 500°C, the heat treatment time is 20 min, cooling to room temperature, and crushing to a particle size of about 10 μm; the crushed particles are dispersed in an ethanol aqueous solution (ethanol accounts for 70wt%) according to a solid-liquid ratio of 1g:8mL, and a 10wt% cyclohexylmethyldimethoxysilane alcohol aqueous solution (ethanol accounts for 50wt%) is added, and the added amount is such that the mass ratio of the crushed particles to cyclohexylmethyldimethoxysilane is 1:0.2, and the passivated silicon-carbon material is fully reacted to obtain;
[0041] (S3) A mixed gas III of acetylene and nitrogen (the volume ratio of acetylene to nitrogen is 1:4) is introduced into the reactor to perform carbon deposition coating on the material. The reaction is maintained for 1 hour. The flow rate of the mixed gas III and the carbon coating time are controlled so that the carbon coating thickness is about 4-6 nm.
[0042] Figure 1 This is a scanning electron microscope image of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention. Figure 2 This is the element distribution diagram of the pre-lithiation silicon-carbon composite material obtained in Example 1 of the present invention. Figure 1 and Figure 2 It can be seen that in the silicon-carbon composite material prepared in Example 1, carbon and silicon elements are evenly distributed.
[0043] Figure 3 This is a first cycle charge and discharge voltage curve of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention.
[0044] Figure 4 The XRD diagram of the pre-lithiation silicon-carbon composite material prepared in Example 1 of the present invention has a relatively obvious silicon crystallization peak.
[0045] Example 2
[0046] The other conditions are the same as those in Example 1, except that in step (S1), the aromatic compound is naphthalene and the aromatic lithium reagent is 5 wt % of the porous carbon mass.
[0047] Example 3
[0048] The other conditions are the same as those in Example 1, except that in step (S1), the mixed gas flow rate and deposition time are controlled so that the silicon content of the silicon-carbon core material is 58.7 wt%.
[0049] Example 4
[0050] The other conditions are the same as those in Example 1, except that in step (S2), in the mixed gas II, the volume ratio of nitrogen to oxygen is 95:5.
[0051] Example 5
[0052] The other conditions are the same as those in Example 1, except that in step (S2), in the mixed gas II, the volume ratio of nitrogen to oxygen is 90:10.
[0053] Example 6
[0054] The other conditions are the same as those in Example 1, except that in step (S2), the amount of cyclohexylmethyldimethoxysilanol aqueous solution added satisfies the mass ratio of the crushed particles to cyclohexylmethyldimethoxysilane of 1:0.3.
[0055] Example 7
[0056] The other conditions are the same as those in Example 1, except that the cyclohexylmethyldimethoxysilanol aqueous solution is replaced by a hexadecylmethyldimethoxysilanol aqueous solution in an amount such that the mass ratio of the crushed particles to hexadecylmethyldimethoxysilanol is 1:0.3.
[0057] Comparative Example 1
[0058] The other conditions are the same as those in Example 1, except that step (S2) is changed to: the silicon-carbon core material obtained in step (S1) is crushed to a particle size of about 10 μm; the crushed particles are dispersed in an ethanol aqueous solution (ethanol accounts for 70 wt%) at a material-liquid ratio of 1 g:8 mL, and a 10 wt% cyclohexylmethyldimethoxysilane aqueous solution is added in an amount that satisfies the mass ratio of the crushed particles to cyclohexylmethyldimethoxysilane of 1:0.2, and the passivated silicon-carbon material is fully reacted. That is, the heat treatment including the mixed gas II is omitted.
[0059] Comparative Example 2
[0060] The other conditions are the same as those in Example 1, except that step (S2) is changed to: introducing a mixed gas II of nitrogen and air with a volume ratio of 99:1 to heat treat the silicon-carbon core material, the heat treatment temperature is 500°C, the heat treatment time is 20 minutes, cooling to room temperature, crushing to a particle size of about 10 μm, and obtaining a passivated silicon-carbon material. That is, the step of silane coupling agent treatment is omitted.
[0061] Comparative Example 3
[0062] The other conditions are the same as those in Example 1, except that step (S1) is changed to porous carbon (BET = 1800m 2 / g) is put into a reactor, and in a nitrogen atmosphere, the temperature is raised to 600°C at a heating rate of 10°C / min, and then a mixed gas I of monosilane gas and nitrogen gas in a volume ratio of 1:4 is introduced to perform silicon deposition to obtain a silicon-carbon core material, and the mixed gas flow rate and deposition time are controlled to make the silicon content of the silicon-carbon core material about 51wt%, and the mixture is cooled and the gas introduced into the mixer is stopped and switched to nitrogen. That is, pre-lithiation of porous carbon is not performed.
[0063] Comparative Example 4
[0064] The other conditions are the same as those in Example 1, except that in step (S2), the cyclohexylmethyldimethoxysilanol aqueous solution is replaced by an HK-560 alcohol aqueous solution of equal mass concentration, and the amount used satisfies the mass ratio of the crushed particles to HK-560 to be 1:0.2.
[0065] Test Case
[0066] The silicon-carbon negative electrode materials provided in the embodiment and the comparative example are assembled into a battery, and the steps are as follows:
[0067] 1. Pole sheet preparation: The negative electrode material, conductive agent (Super-P), and polyacrylic acid (PAA) binder are mixed in a mass ratio of 80:10:10 to prepare a slurry, stirred and mixed, and then coated on the copper foil current collector. After drying at room temperature, it is placed in a vacuum oven and further dried at 60°C under vacuum conditions for 12 hours to obtain a pole sheet.
[0068] 2. Battery assembly: The above-obtained electrode pieces are cut into circular pieces with a diameter of 10 mm and an active material loading of 1.3 mg / cm 2 ; Metal lithium sheet was used as the counter electrode, 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, with 5% volume of fluoroethylene carbonate added) as the electrolyte, and a polypropylene microporous membrane was assembled into a 2032 type button cell in an argon atmosphere glove box, with 50 μL of electrolyte added to each cell.
[0069] The obtained 2032 button battery was subjected to electrical performance test: the charge and discharge cut-off voltages were 1.5V and 0.005V, respectively, and then activated at 0.05C rate and charged and discharged at 1C rate for cycle testing. Figure 1 1 is a typical first cycle charge and discharge curve of the silicon-carbon composite material obtained in the example, and Table 1 is the electrochemical performance results of different materials.
[0070] Table 1 Electrochemical performance test of silicon-carbon negative electrode materials
[0071] .
[0072] It can be seen from the data in Table 1 that the pre-lithiation silicon-carbon composite material prepared by the present invention has high capacity, first effect and long cycle performance. This is attributed to the special structure of the silicon-carbon composite material of the present invention, with the pre-lithiation silicon-carbon material as the core, and the intermediate passivation layer is obtained by sequentially subjecting the silicon-carbon core material to heat treatment with an oxygen-containing gas and modification with a silane coupling agent, and finally carbon coating as a shell layer. The silicon-carbon composite material with this structure can improve the first effect of the material by compensating for the irreversible lithium loss in the discharge process through pre-lithiation; by partially oxidizing the surface interface and bonding with the silane coupling agent to form an organic passivation layer to reduce expansion and avoid side reactions with the electrolyte, thereby improving the capacity retention rate of the material and having excellent electrochemical properties.
Claims
1. A pre-lithiation silicon-carbon composite material, characterized in that: The invention has a three-layer composite structure, which comprises a pre-lithiated silicon-carbon core, an intermediate passivation layer and a carbon coating layer from the inside to the outside. The pre-lithiated silicon-carbon core is obtained by compounding a pre-lithiated reagent and porous carbon and then undergoing silicon deposition. The silicon-carbon core contains 40-70wt% nano silicon particles. The intermediate passivation layer is obtained by first subjecting the silicon-carbon core material to calcination with an oxygen-containing gas and then to surface modification with a silane coupling agent, wherein the silane coupling agent contains a C6-C16 straight chain, branched chain or cycloalkane. The silicon-carbon core material is first calcined with an oxygen-containing gas in a mixed gas II of an oxygen-containing gas and an inert gas, wherein the oxygen-containing gas is selected from at least one of oxygen, carbon dioxide, carbon monoxide, sulfur dioxide, water vapor, methanol vapor and ethanol vapor, and the oxygen-containing gas accounts for 1-5% of the volume of the mixed gas II. Alternatively, the oxygen-containing gas is air, and the amount of oxygen used is such that the oxygen accounts for 1-5% of the volume of the mixed gas II.
2. A method for preparing a pre-lithiated silicon-carbon composite material, characterized in that: The following steps are involved: (S1) uniformly mixing a pre-lithiation reagent solution and porous carbon, and after sufficient pre-lithiation, performing solid-liquid separation and solid-phase calcination to obtain a pre-lithiation carbon substrate; placing the pre-lithiation carbon substrate in a reaction furnace, introducing a mixed gas I of silane gas and an inert gas under an inert atmosphere, and performing silicon deposition under heating conditions to obtain a silicon-carbon core material; (S2) introducing a mixed gas II of oxygen-containing gas and inert gas into a reaction furnace, heating to 500-800° C. to heat-treat the silicon-carbon core material obtained in step (S1), pulverizing the material after cooling, dispersing the pulverized particles in an alcohol aqueous solution, adding an alcohol aqueous solution containing a silane coupling agent, and obtaining a passivated silicon-carbon material after reaction; the silane coupling agent contains a C6-C16 straight chain, branched chain, or cycloalkane; the oxygen-containing gas is selected from at least one of oxygen, carbon dioxide, carbon monoxide, sulfur dioxide, water vapor, methanol vapor, and ethanol vapor; in the mixed gas II, the oxygen-containing gas accounts for 1-5% of the volume of the mixed gas II; or the oxygen-containing gas is air, and the amount of oxygen used is such that the oxygen accounts for 1-5% of the volume of the mixed gas II; (S3) The passivated silicon-carbon material is carbon-coated to obtain a pre-lithiation silicon-carbon composite material.
3. The preparation method according to claim 2, characterized in that: In step (S1), the pre-lithiation reagent is a complex of lithium and an aromatic compound, and the aromatic compound is selected from at least one of biphenyl, dimethylbiphenyl, naphthalene, anthracene, and phenanthrene; the pre-lithiation is to immerse the porous carbon in a solution containing the pre-lithiation reagent, react at 40-50°C for 10-20h, and sinter the obtained slurry.
4. The preparation method according to claim 3, characterized in that: The pre-lithiation reagent solution is obtained by reacting a lithium source and an aromatic compound in an organic solvent, wherein the lithium source is selected from at least one of lithium element, lithium carbonate and lithium hydroxide, the aromatic compound is selected from at least one of biphenyl, dimethyl biphenyl, 4,4'-di-tert-butyl biphenyl, naphthalene, anthracene and phenanthrene, and the organic solvent is selected from at least one of tetrahydrofuran, 2-methyltetrahydrofuran, diethylene glycol dimethyl ether and methyl tert-butyl ether; the sintering temperature is 500-700°C and the sintering time is 5-10h.
5. The preparation method according to claim 2, characterized in that: In step (S1), the specific surface area of the porous carbon is 1500-2500 m 2 / g; the amount of pre-lithiation reagent is 5-10wt% of the porous carbon mass.
6. The preparation method according to claim 2, characterized in that: In step (S1), the silane is selected from at least one of monosilane, disilane, trichlorosilane and dichlorosilane; and / or The amount of silane gas introduced is sufficient to satisfy the silicon mass ratio of the obtained silicon-carbon core to be 40-70wt%; and / or In the mixed gas I, the volume ratio of silane gas to inert gas is 1:1-4; and / or The heating condition during silicon deposition is 500-900°C.
7. The preparation method according to claim 2, characterized in that: In step (S2), the heat treatment time is 10-30 minutes.
8. The preparation method according to claim 2, characterized in that: In step (S2), the alcohol aqueous solution is a mixture of at least one of methanol, ethanol, and propanol and water, wherein the alcohol accounts for 50-70wt%; the ratio of the alcohol aqueous solution to the crushed particles is 5-8mL:1g.
9. The preparation method according to claim 2, characterized in that: In step (S2), the silane coupling agent is selected from at least one of cyclohexylmethyldimethoxysilane, dodecylmethyldimethoxysilane, and hexadecylmethyldimethoxysilane; the concentration of the alcohol aqueous solution of the silane coupling agent is 5-10wt%, and the amount of the alcohol aqueous solution of the silane coupling agent satisfies the mass ratio of the silane coupling agent to the crushed particles of 0.2-0.3:
1.
10. The preparation method according to claim 2, characterized in that: In step (S3), carbon coating is carried out by introducing a carbon-containing process gas and heating at 500-800°C, wherein the carbon-containing process gas is selected from at least one of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, acetylene, propyne, and butyne; the amount of carbon-containing process gas introduced satisfies the carbon coating layer thickness of 1-10nm.
Citation Information
Patent Citations
Lithium-silicon-carbon composite negative electrode material as well as preparation method and application thereof
CN117996050A
Slurry-stable lithiated silicon-based composite material as well as preparation method and application thereof
CN113437280A
Lithium-doped silicon-carbon composite material and preparation method thereof
CN118213516A